Malnutrition outweighs the effect of the obesity paradox - Suriya Prausmüller; Gregor Heitzinger; Noemi Pavo; Georg Spinka; Georg Goliasch; Henrike Arfsten; Cornelia Gabler; Guido Strunk; Christian Hengstenberg; Martin Hülsmann; Philipp E. Bartko (Wiley, 2022)
Abstract Background High body mass index (BMI) is paradoxically associated with better outcome in patients with heart failure (HF). The effects of malnutrition on this phenomenon across the whole spectrum of HF have not yet been studied. Methods In this observational study, patients were classified by guideline diagnostic criteria to one of three heart failure subtypes: reduced (HFrEF), mildy reduced (HFmrEF), and preserved ejection fraction (HFpEF). Data were retrieved from the Viennese‐community healthcare provider network between 2010 and 2020. The relationship between BMI, nutritional status reflected by the prognostic nutritional index (PNI), and survival was assessed. Patients were classified by the presence (PNI < 45) or absence (PNI ≥ 45) of malnutrition. Results Of the 11 995 patients enrolled, 6916 (58%) were classified as HFpEF, 2809 (23%) HFmrEF, and 2270 HFrEF (19%). Median age was 70 years (IQR 61-77), and 67% of patients were men. During a median follow‐up time of 44 months (IQR 19-76), 3718 (31%) of patients died. After adjustment for potential confounders, BMI per IQR increase was independently associated with better survival (adj. hazard ratio [HR]: 0.91 [CI 0.86-0.97], P = 0.005), this association remained significant after additional adjustment for HF type (adj. HR: 0.92 [CI 0.86-0.98], P = 0.011). PNI was available in 10 005 patients and lowest in HFrEF patients. PNI was independently associated with improved survival (adj. HR: 0.96 [CI 0.95-0.97], P < 0.001); additional adjustment for HF type yielded similar results (adj. HR: 0.96 [CI 0.96-0.97], P < 0.001). Although obese patients experienced a 30% risk reduction, malnutrition at least doubled the risk for death with 1.8‐ to 2.5‐fold higher hazards for patients with poor nutritional status compared with normal weight well‐nourished patients. Conclusions The obesity paradox seems to be an inherent characteristic of HF regardless of phenotype and nutritional status. Yet malnutrition significantly changes trajectory of outcome with regard to BMI alone: obese patients with malnutrition have a considerably worse outcome compared with their well‐nourished counterparts, outweighing protective effects of high BMI alone. In this context, routine recommendation towards weight loss in patients with obesity and HF should generally be made with caution and focus should be shifted on nutritional status.